Acute Respiratory Decompensation Requiring Intubation in Pregnant Women with SARS-CoV-2 (COVID-19) - Jenna S. Silverstein; Meghana A. Limaye; Sara G. Brubaker; Ashley S. Roman; Judita Bautista; Judith Chervenak; Adam J. Ratner; Philip M. Sommer; Nicole M. Roselli; Charlisa D. Gibson; David Ellenberg; Christina A. Penfield (American Journal of Perinatology Reports, 2020)
There is a current paucity of information about the obstetric and perinatal outcomes of pregnant novel coronavirus disease 2019 (COVID-19) patients in North America. Data from China suggest that pregnant women with COVID-19 have favorable maternal and neonatal outcomes, with rare cases of critical illness or respiratory compromise. However, we report two cases of pregnant women diagnosed with COVID-19 in the late preterm period admitted to tertiary care hospitals in New York City for respiratory indications. After presenting with mild symptoms, both quickly developed worsening respiratory distress requiring intubation, and both delivered preterm via caesarean delivery. These cases highlight the potential for rapid respiratory decompensation in pregnant COVID-19 patients and the maternal-fetal considerations in managing these cases.